Hindu-Muslim violence in Gujarat, 2002: political logic, spatial configuration, and communal cooperation - Dhattiwala, R (2013)
This thesis uses a mixed methods approach to investigate the different levels of Hindu-Muslim violence in Gujarat (western India) in 2002 when at least a thousand Muslims were killed. An original dataset of killings is compiled to analyse macrospatial variation in the violence across towns and rural areas of Gujarat. Data collected from 21 months of ethnographic fieldwork in Ahmedabad city is used to investigate microspatial variation across three neighbourhoods with varying levels of violence. Macrospatial analysis discusses the link between political authority and its capacity to instigate ethnic violence as a response to electoral calculations and identifies the mechanisms by which violence against Muslims was orchestrated by the Hindu nationalist Bharatiya Janata Party (BJP). Ethnographic findings demonstrate the importance of ecological strategies adopted by attackers and targets during the course of attack and urge a re-examination of the intuitive association of spatial proximity with greater interethnic contact. Findings also reveal methods of enforcement used by legitimate and illegitimate institutions of a peaceful slum neighbourhood in resolving commitment problems of cooperation. Finally, the thesis examines the aftermath of the violence, more specifically a political phenomenon of Muslims of Gujarat supporting the BJP nine years after the brutal violence. Methodologically, the main contribution of this thesis is in bridging the quantitative and ethnographic traditions in the sociology of ethnic violence to make possible the linking, and disentangling, of macrolevel risk factors associated with violence from microlevel factors. Findings of the thesis hopefully provide a better understanding of ethnic violence in multi-ethnic democracies and a roadmap of policy-making for India as it continues to struggle with ethnic strife.